2019
DOI: 10.3390/biology8030063
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis and Metabolic Profiling of Lycoris Radiata

Abstract: Lycoris radiata belongs to the Amaryllidaceae family and is a bulbous plant native to South Korea, China, and Japan. Galantamine, a representative alkaloid of Amaryllidaceae plants, including L. radiata, exhibits selective and dominant acetylcholinesterase inhibition. In spite of the economic and officinal importance of L. radiata, the molecular biological and biochemical information on L. radiata is relatively deficient. Therefore, this study provides functional information of L. radiata, describe galantamine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
54
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 60 publications
(66 reference statements)
4
54
0
Order By: Relevance
“…The enzyme responsible for tyramine biosynthesis is the tyrosine decarboxylase (TYDC) ( Figure 2). Two gene transcript variants of TYDC, named TYDC1 and TYDC2, were identified from the transcriptome of different Amaryllidaceae species including N. pseudonarcissus [41], Narcissus papyraceus [42], Lycoris radiata [43], and L. aureus [44].…”
Section: Biosynthesis Of Amaryllidaceae Alkaloidsmentioning
confidence: 99%
See 2 more Smart Citations
“…The enzyme responsible for tyramine biosynthesis is the tyrosine decarboxylase (TYDC) ( Figure 2). Two gene transcript variants of TYDC, named TYDC1 and TYDC2, were identified from the transcriptome of different Amaryllidaceae species including N. pseudonarcissus [41], Narcissus papyraceus [42], Lycoris radiata [43], and L. aureus [44].…”
Section: Biosynthesis Of Amaryllidaceae Alkaloidsmentioning
confidence: 99%
“…Specifically, l-phenylalanine is converted to trans-cinnamic acid by the phenylalanine ammonia-lyase (PAL) ( Figure 2). Several PAL gene transcripts were identified and characterized from different species of Amaryllidaceae [41][42][43][47][48][49]. Interestingly, two main phylogenetic PAL clusters were identified; the first one contained PAL transcripts ubiquitously expressed in Amaryllidaceae whereas the second cluster contained PAL transcripts with expression highest and correlating with organs where AAs accumulated [26].…”
Section: Biosynthesis Of Amaryllidaceae Alkaloidsmentioning
confidence: 99%
See 1 more Smart Citation
“…TYDC is an important enzyme, which catalyzes the production of tyramine from L-tyrosine [ 68 ]. It has been found that two transcript variants of TYDC are present in Amaryllidaceae alkaloid producing plants [ 59 , 65 , 66 , 69 , 70 ]. The phylogenetic analysis showed that Amaryllidaceae TYDCs can be divided into two main clusters: “TYDC1” and “TYDC2” [ 59 ].…”
Section: Biotechnological Production Of Amaryllidaceae Alkaloidsmentioning
confidence: 99%
“…N4OMT has been identified and characterized in many Amaryllidaceae alkaloid producing plants [ 59 ]. The expression analyses showed that N4OMT is highly expressed in bulbs [ 59 , 65 , 70 , 72 ]. Interestingly, the O -methyltransferase found in Lycoris aurea (LauOMT1) was expressed at highest levels in flowers stalks and ovaries, and was demonstrated to have both para ’ and meta ’ O -methylation activities with a strong preference for the meta ’ position methylation [ 73 ].…”
Section: Biotechnological Production Of Amaryllidaceae Alkaloidsmentioning
confidence: 99%